Future Trends of Data Management - Niitamo, Olavi E.; Janhunen, Olli (Tilastokeskus, 1983)
Olavi E. Niitamo: Data Management in the 1980s, Olli Janhunen: Integration of Data, Applications and the Mass Media
Keywords: tilastot; tiedonhallinta; Tutkimuksia, Working Papers